Ri cang Song Yuan chan seng mo ji xuan bian - Jiang, Jing (Xi nan shi fan da xue chu ban she, 2015)
Beschreibung
Keywords: Zen calligraphy / China; Calligraphy, Chinese / History / Song-Yuan dynasties, 960-1368; Calligraphy, Chinese / Song-Yuan dynasties; Zen calligraphy; China